Storm-Induced Predator-Prey Decoupling Promotes Springtime Accumulation of North Atlantic Phytoplankton - Morison, Francoise; Harvey, Elizabeth; Franzè, Gayantonia; Menden-Deuer, Susanne (Frontiers in Marine Science, 2019)
During NAAMES May 2016 field campaign, we examined the response of plankton population dynamics to rapid re-stratification of surface waters following a deep mixing event in the subpolar North Atlantic. Over the 4-day occupation of a station, we measured phytoplankton growth and grazer/virus-induced mortality rates in dilution assays conducted across a range of light intensities. Rates were estimated from changes in chlorophyll a and the abundance of three phytoplankton groups identified by flow cytometry. Initially, biological and physical water column properties were homogeneous down to >200 m, followed by rapid shoaling of the mixed layer to 20-30 m. Initial in situ chlorophyll a concentration was 0.4 µg L-1, and phytoplankton biomass accumulated at an average rate of 0.4 d-1 over the next two days. When mixed layer depth was maximal, there were no mortality losses and phytoplankton growth rates increased with increased light intensity. After shoaling, grazing rates increased, but never matched the magnitude of phytoplankton growth rates. When the mixed layer was shallowest, growth rates exceeded >1 d-1 at all non-dark light intensities. Chlorophyll a based grazing rates were consistent across light levels (~0.3 d-1) and were highest on Synechococcus (0.3-0.6 d-1) and lowest on pico-eukaryotes (~0.2 d-1). The delay with which grazing resumed resulted in growth exceeding losses and consumption of an average of 30% of primary production. Virus-induced mortality rates were minimal across all mixing profiles and light intensities. Overall, both chlorophyll a and group-specific phytoplankton accumulation rates predicted from the shipboard experiments matched those in situ, suggesting that incubation conditions faithfully captured the growth and loss processes governing in situ population dynamics. The observations made here indicate that transient deepening of the mixed layer followed by rapid stratification provided conditions under which phytoplankton escape protistan grazing and accumulate biomass. During the physically dynamic springtime in the North Atlantic, frequent ephemeral fluctuations in the depth of mixing may represent an important mechanism governing the formation and the magnitude of the North Atlantic spring bloom.